1999
DOI: 10.4278/0890-1171-13.6.319
|View full text |Cite
|
Sign up to set email alerts
|

Do Blue-Collar Workers Perceive the Worksite Health Climate Differently Than White-Collar Workers?

Abstract: A mail survey was distributed to a random sample of 497 both blue- and white-collar workers employed at a large manufacturing company to measure dimensions of worksite health climate: organizational and interpersonal support, and health norms. Statistically significant differences were observed for nearly all aspects of the dimensions with white-collar workers having more positive perceptions than blue-collar workers. The study suggests that future research explore how these perceptions may be enhanced and wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 6 publications
3
46
0
1
Order By: Relevance
“…Examples of these are safety analyses in health care settings [19], in the manufacturing sector [8], in airport ground handling operations [20], in construction sites [21,22,23], in clerical and service organizations [17], and in road administration [24]. Additionally, comparative analyses between managers' and employees' perceptions [25], highand low-accident organizations [11], individual-and organizational-level climate perceptions [8,11,12], and between blue-and white-collar workers [26] have been carried out.…”
Section: Perceptions Of Safety Climatementioning
confidence: 99%
“…Examples of these are safety analyses in health care settings [19], in the manufacturing sector [8], in airport ground handling operations [20], in construction sites [21,22,23], in clerical and service organizations [17], and in road administration [24]. Additionally, comparative analyses between managers' and employees' perceptions [25], highand low-accident organizations [11], individual-and organizational-level climate perceptions [8,11,12], and between blue-and white-collar workers [26] have been carried out.…”
Section: Perceptions Of Safety Climatementioning
confidence: 99%
“…DeJoy, Murphy and Gershon's analyses in health care settings [5], Diaz and Cabrera's analyses on airport ground handling operations [6] and Niskanen's study on road administration [7] are examples of such studies. Additionally, comparative analyses between managers' and employees' perceptions [4], high-and lowaccident organizations [3], individual-and organizational-level climate perceptions [8,9] and between blue-and white-collar workers [10] have been carried out. What most of these studies revealed is that workers differ in their attitudes to safety issues and in their perceptions of workplace hazards.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated participation rates in workplace health promotion programs differ by gender 71 and socioeconomic status. 72,73 Female employees were more reactive to environmental changes (e.g. snacks offered in cafeterias) and blue-collar employees perceived less emphasis on health in the workplace.…”
Section: A Variety Of Services With Broad Appeal To the Employee Popumentioning
confidence: 99%
“…74 Blue-collar workers may be especially sensitive to this, as one survey found blue-collar workers more likely than white-collar workers to perceive a lack of concern for health among their supervisors. 72 Berry et. al.…”
Section: Engagement Of Leadership At All Levels To Support Implementamentioning
confidence: 99%